HLA-B*44 is associated with a more than twentyfold increase in cyclic citrullinated peptide antibody serum level in Croatian patients with seropositive rheumatoid arthritis - Jure Aljinović; Darko Kero; Daniela Šošo; Marin Petrić; Daniela Marasović Krstulović; Dijana Perković; Esma Čečuk-Jeličić; Sonja Jaman; Dora Dujmović; Ivanka Marinović (PLoS ONE, 2025)
Objectives To determine whether any of the HLA-A*, HLA-B* and HLA-DR* alleles in seropositive rheumatoid arthritis (RA) can be associated with the extreme serum levels of rheumatoid factor (RF) and cyclic citrullinated peptide antibodies (anti-CCP). Methods This was a retrospective cross-sectional study of adult patients. Demographic data, HLA typing data and RF and anti-CCP levels were collected and analysed. Results HLA-A*02, HLA-B*44 and HLA-DRB1*04 were more prevalent in patients from the RA cohort compared to healthy controls. Intra-cohort analysis revealed that HLA-B*44 had an increased frequency of a twenty-fold increase in anti-CCP (P = 0.033) and HLA-A*03 had a borderline (P = 0.063) frequency. HLA-A*03 was more frequent in the groups with >3-fold and >10-fold anti-CCP levels, while HLA-DRB1*04 was of borderline significance at >3-fold anti-CCP increase (P = 0.053). HLA-B*08 showed a lower frequency of 3-, 10- and 20-fold increase in anti-CCP serum levels. Carriers of B*44 (OR = 5.58; P = 0.030), DRB1*04 (OR = 3.89; P = 0.027) or A*03 (OR = 2.71; P = 0.023) were statistically significantly more likely to have a 20-fold increase in anti-CCP levels over the diagnostic threshold. None of the alleles increased the likelihood of having high or extreme RF levels. Conclusions HLA-B*44 is associated with a twenty-fold increase in anti-CCP serum levels. HLA-A*03 and HLA-DRB1*04 have a positive trend towards a twenty-fold increase in anti-CCP levels. Earlier aggressive therapy in these patients can prevent such an extreme increase in antibody levels.